CHARACTERISTICS OF ORGANIZATIONAL STRUCTURE OF BOSNIAN AND HERZEGOVINIAN COMPANIES - Adisa Delić; Emira Ahmetović (Economic Review)
The technological revolution (especially in the field of information and communications technology) and globalization are the key factors in shaping the new competitive landscape which is characterized by hypercompetition, increasing consumer demands and increasing demands for innovation, knowledge and learning. Modern enterprises along with the emerging business environment must appropriately adjust, and one of the preconditions for their successful adaptation is also the choice of an appropriate organizational design. Organizational structure, as the most important element of organizational design, is there today to provide companies with propulsion of internal and external borders. Consequently, the analysis of recent trends in the design of the organization in the context of adapting the enterprise global dynamic environment is one of the goals of this paper. In addition, this study will also include the results of the empirical study whose purpose was, among other things, the identification and analysis of the dominant type of organizational structure of the enterprises in Bosnia and Herzegovina. The results of this research will demonstrate the extent to which the structure of these companies is in accordance with the new trends in the field of organization.